Experimental design for biologists - Glass, David J (New York : CSHL., 2014)
The effective design and analysis of experiments in biology are critical to success, yet graduate students in biological and medical sciences typically receive very little formal training in these steps. With feedback from readers of the first edition, colleagues, and students taking the very popular experimental design courses taught by the author, this second edition of Experimental Design for Biologists retains the engaging writing style while organizing the book around the four elements of experimental design: the framework, the system, the experiment, and the model. The approach has been tested in the classroom, where the author has taught numerous graduate students, MD/PhD students, and postdoctoral fellows. The goal of every scientist is to discover something new and with the aid of Experimental Design for Biologists, this task is made a little easier.
Index 283-289p.
Keywords: Assumption controls; System validation; Defining scientific